Tingkahlaku Politik Etnis Tionghoa Pada Pemilukada 2010 Di Kota Medan - Lidya Mahdalena (Dinamika Politik, 2012)
This study is the study of the political behavior of ethnic Chinese in the 2010 General Election in Kelurahan Pusat Pasar, Kecamatan Medan Kota. The focus is on what the reasons discussed ethnic Chinese community in Kelurahan Pusat Pasar, Kecamatan Medan Kota vote at the General Election of 2010. The findings of this study, among others, there are four reasons the ethnic Chinese community vote at the General Election of 2010, the first, they assume the right to vote is part of human rights. Secondly, participating in elections is an obligation for citizens. Third, the right to vote of citizens as a means of implementing democracy in elections. Fourth, participate in determining their leaders through elections. The method used is descriptive-qualitative method that is intended to describe an event in more detail.Keywords: Political behavior, Political Participation, Election.